Munatakhabe Śāhanāme, īāne, Irāṇṇa deśanāṃ Pārasīonāṃ pādaśāhonī tavārīkhanī Śāhanāmāṃ nāmmanī moṭī ketāba jo śāyera Phīradosī Tusīe āsare gīāṃ 900 varasonī vātapara lakhī hatī te madhethī hālanāṃ Pārasīonāṃ bujarago, javānno, temaja bālakone vāñcī vākepha thavā joga cuṇṭī kāhāḍelā asala betonuṃ nāndhaluṃ pusataka keṭalīeka tasavīro sāthe : e madhe Phīradosīnī jīndagīnā hevāla tathā Pārasīonāṃ pādaśāhoni tavārīkha, temaja bījī bābado vīse Gujarātī bhāśāmāṃ ketaloeka kholāso kīdho che - Firdawsī (Ejukeśana Sosāīṭī Paresa, 1865)
Selections from Firdawsī's Shāhnāmah, classical versified historical accounts of ancient Persian monarchs; includes critical interpretation in Gujarati and brief note on Firdawsī